2016
DOI: 10.1245/s10434-016-5203-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Quality of Life Study for Colorectal Cancer Patients with Peritoneal Carcinomatosis Undergoing Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy

Abstract: QoL after CRS and HIPEC improved or returned to baseline in all categories by 6-12 months after surgery. Patient selection is important not only for improved survival but also for improved QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 19 publications
6
51
1
Order By: Relevance
“…We have done retrospective and prospective studies looking at the quality of life of our patients after CRS and HIPEC. Our studies, as well as other quality of life studies, have shown that while the quality of life drops immediately after CRS and HIPEC, the patients return to baseline by 6 months [34][35][36].…”
Section: Discussionsupporting
confidence: 64%
“…We have done retrospective and prospective studies looking at the quality of life of our patients after CRS and HIPEC. Our studies, as well as other quality of life studies, have shown that while the quality of life drops immediately after CRS and HIPEC, the patients return to baseline by 6 months [34][35][36].…”
Section: Discussionsupporting
confidence: 64%
“…Two recent studies reported decreased QoL and increased symptoms 6–12 months after HIPEC treatment. And this was also observed in patients without postoperative complications [24, 25]. …”
Section: Discussionmentioning
confidence: 69%
“…Although there was no difference in major morbidity or presence of a stoma between patients treated with either concentration‐ or BSA‐based HIPEC, HRQOL was lower at the end of follow‐up (3 months postoperative) in the HIPEC‐CONC group. However, a longer follow‐up period is appropriate to make sound conclusions regarding HRQOL as in literature HRQOL is reported to drop 3 to 4 months after CRS and HIPEC and returns to preoperative values, 6 to 12 months postoperative …”
Section: Discussionmentioning
confidence: 98%
“…In the HIPEC‐BSA group, the presence of a stoma was positively correlated with a decreased SF‐36 sum score at discharge. Several studies reported the presence of a stoma at 3 or 6 months postoperative to be associated with lower HRQOL . Three months postoperative, average HRQOL returned to preoperative values in contrast to patients treated with concentration‐based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%